Student Response of Elementary School Teacher Education to Mini Workshop Learning Video Through Smartphone - Yuliyanto, Aan; Herawati, Herawati; Maulana, Sandi (Arfah BHMS Foundation, 2025)
Prospective teacher students should be able to make learning videos to support digital learning. This study aims to understand the responses of prospective elementary school teachers in making learning videos through Mini-Workshops. This study used survey methods and data analysis techniques that were carried out descriptively on questionnaires for 13 second-semester students of the Elementary School Teacher Education study program at a private campus in Indramayu. Regarding the mini-workshop, the significant aspect is considered very helpful and effective in supporting the making of videos. Aspects of the activity description are considered attractive, creative, and straightforward. The novelty aspect is considered excellent and quite innovative. The carrying capacity aspect is considered motivating and fulfilling expectations in making videos. In video projects, students are highly motivated to complete videos and find it relatively easy to compose video materials and scenarios and collaborate, but they have difficulty editing videos. Making videos via smartphones will be accessible when they often practice and pay attention to recording techniques. Internet stability and storage capacity must be considered when doing and exporting video edits. Informative learning videos supported by valid and reliable references. Obstacles to making videos come from self-confidence, time management, and less-than-optimal collaboration. The Mini-Workshop is considered capable of exploring the potential of Elementary School Teacher Education students in designing learning videos